Genome-Wide Identification and Functional Characterization of the Chloride Channel TaCLC Gene Family in Wheat (Triticum aestivum L.) - Mao, Peijun; Run, Yonghang; Wang, Hanghui; Han, Changdong; Zhang, Lijun; Zhan, Kehui; Xu, Haixia; Cheng, Xiyong (Frontiers in Genetics, 2022)
In plants, chloride channels (CLC) contribute to a number of specific functions, such as regulation nutrient transport and stress tolerance. Members of the wheat TaCLC gene family have been proposed to encode anion channels/transporters that may be related to nitrogen transportation. To better understand their role, TaCLC family was screened and 23 TaCLC gene sequences were identified using an Hidden Markov Model in conjunction with a wheat genome database. Gene structure, chromosome location, conserved motif, and expression pattern of the resulting family members were then analyzed. Phylogenetic analysis showed that the TaCLC family is divided into two subclasses (I and II) and 7 clusters (-a, -c1, -c2, -e, -f1, f2, -g2). Using a wheat RNA-seq database, the expression pattern of TaCLC family members was determined to be that of an inducible expression type. In addition, 7 genes from 7 different clusters were selected for quantitative real-time PCR (qRT-PCR) analysis under low nitrogen stress or salt stress conditions, respectively. The results indicated that the gene expression levels of this family were up-regulated under low nitrogen stress and salt stress, except for TaCLC-c2 which was from subfamily -c. The yeast complementary experiments illustrated that TaCLC-a-6AS-1, TaCLC-c1-3AS, and TaCLC-e-3AL all had anion transport functions of NO3- or Cl- and compensated the hypersensitivity of yeast GEF1 mutants strain YJR040w (Δgef1) in restoring anion-sensitive phenotype. The above results will establish a theoretical foundation for further functional characterization of TaCLCs and provide an initial reference for better understanding nitrate nitrogen transportation in wheat.